PEMANFAATAN PASIR GUNUNG MARAPI SUMATERA BARAT DALAM CAMPURAN BETON - Mulyati Mulyati; Al Furqan Syofian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the characteristics and potential use of eruption sand from Mount Marapi, West Sumatra as a substitute for fine aggregate in concrete mixtures. Mount Marapi sand is abundantly available, but its use in the construction industry is not yet optimal, therefore it is necessary to study its quality in more depth. The characteristics of Mount Marapi sand were tested including grain gradation, organic content, mud content, bulk density, specific gravity and water absorption. Variations in concrete mixes were made with the percentage of Mount Marapi sand used compared to river sand being 0%, 50%, 75%, and 100%. Concrete compressive strength testing was carried out at the age of 28 days with a cylindrical test specimen for a design compressive strength of 27.5 MPa. The research results show that Mount Marapi sand has rather coarse grains, low mud content and water absorption. The use of Mount Marapi sand as a substitute for river sand produces concrete that has a higher compressive strength than normal concrete, the highest compressive strength was obtained when using 100% Mount Marapi sand, namely 31.54 MPa, an increase of 14.36%. Thus, Mount Merapi eruption sand can be used as a substitute for fine aggregate in concrete mixes.Keywords: Mount Marapi sand, fine aggregate, concrete compressive strength, volcanic material